A review of saponin intervention in metabolic syndrome suggests further study on intestinal microbiota. (October 2020) - Luo, Zichen; Xu, Weichen; Zhang, Ying; Di, Liuqing; Shan, Jinjun
Graphical abstract: Abstract: Metabolic syndrome (MetS) is a series of symptoms including insulin resistance, obesity, dyslipidemia, elevated fasting blood glucose levels, and hepatic steatosis. As a key criterion in MetS, the onset of insulin resistance is related to abnormal levels of circulating free fatty acids and adipokines. It has been discovered in recent years that metabolites and pathogen-associated molecular patterns of intestinal/gut microbiota are also important factors that cause insulin resistance and MetS. Saponins are the main components of many botanicals and traditional Chinese medicines (TCMs), such as ginseng, platycodon, licorice, and alfalfa. They have poor bioavailability, but can be transformed into secondary glycosides and aglycones by intestinal microbiota, further being absorbed. Based on in vivo and in vitro data, we found that saponins and their secondary metabolites have a preventive effect on MetS, and the effective targets are distributed in the intestine and other organs in human body. Intestinal targets involve pancreatic lipase, dietary cholesterol, and intestinal microbiota. Other targets include central appetite, nuclear receptors such as PPAR and LXR, AMPK signaling pathway and adipokines levels, etc. In view of the poor bioavailability of saponins, it is inferred that targets for prototype-saponins to interfere with MetS is mainly located in the intestine, and the activation of other targets may be related to secondary glycosides and aglycones transformed from saponins by intestinal flora. We suggest that the role of intestinal microbiota in saponin intervention in MetS should be further investigated.